Ajrakh: From Caste Dress to Catwalk. (2nd July 2016) - Edwards, Eiluned Mair
Abstract : Ajrakh is a double-sided, block-printed textile worn as caste dress by cattle herders in the desert regions of Kachchh and Thar in north-west India and Sindh in Pakistan, where it is made by Khatri artisans. Readily identified by its distinctive combination of geometric and floral designs, traditional ajrakh is notably printed on both sides of the cloth and is dyed with indigo and madder. In the past forty years ajrakh has not only been transformed from a rustic block print into a popular fashion fabric, it has also become the signature cloth of the Khatri communities at Dhamadka and Ajrakhpur in Kachchh and is their most successful product. This article analyses the interventions that led to the successful adaptation of ajrakh as a regional product to a modern design milieu. It discusses early government initiatives that resulted in the introduction of artisan-designer collaborations in the 1970s, as well as later design developments that were led by Indian and foreign entrepreneurs. It traces the continuing trajectory of ajrakh from rural western India to the catwalks of New Delhi, Mumbai and beyond. Case studies of three fashion companies illuminate the factors that have influenced the commercial ascent of ajrakh . This textile is also considered in respect of recent initiatives to organise and protect the craft sector by the Government of India and by non-governmental organisations. In a final section, the article appraises the value of ajrakh as both a successful commodity and a cultural asset.